2008
DOI: 10.1074/jbc.m709886200
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Association of the Polycomb Group Proteins with Cytokine Genes in Differentiated T Helper Cells

Abstract: The cytokine transcription profiles of developing T helper 1 and T helper 2 cells are imprinted and induced appropriately following stimulation of differentiated cells. Epigenetic regulation combines several mechanisms to ensure the inheritance of transcriptional programs. We found that the expression of the polycomb group proteins, whose role in maintaining gene silencing is well documented, was induced during development in both T helper lineages. Nevertheless, the polycomb proteins, YY1, Mel-18, Ring1A, Ezh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
62
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 106 publications
5
62
2
Order By: Relevance
“…These factors may in turn recruit other factors such as chromatin-modifying enzymes to the Th2 LCR and other regulatory regions of the Th2 cytokine locus. It has been shown that the ATP-dependent chromatin remodeling factor BRG-1 and Polycomb Group proteins such as YY-1, Mel-18, Ring1A, Ezh2, and Eed are recruited to RHS7, as well as il4 promoter and several regulatory elements in the Th2 cytokine locus (36)(37)(38). These chromatin-modifying factors may induce chromatin remodeling and intra-and interchromosomal interactions.…”
Section: Discussionmentioning
confidence: 99%
“…These factors may in turn recruit other factors such as chromatin-modifying enzymes to the Th2 LCR and other regulatory regions of the Th2 cytokine locus. It has been shown that the ATP-dependent chromatin remodeling factor BRG-1 and Polycomb Group proteins such as YY-1, Mel-18, Ring1A, Ezh2, and Eed are recruited to RHS7, as well as il4 promoter and several regulatory elements in the Th2 cytokine locus (36)(37)(38). These chromatin-modifying factors may induce chromatin remodeling and intra-and interchromosomal interactions.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, it was also reported that recruitment of Ezh2 was required for both IFN-g and IL-4 production in differentiated Th1 and Th2 cells. 28 The polycomb repressive complex (PRC) proteins form 2 closely related complexes-PRC2 and PRC1. H3K27 trimethylation is catalyzed by the methyltransferases Ezh2 or Ezh1, 29 which are core components of PRC2 along with Suz12 and Eed.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Previous studies demonstrate that IFN-g-producing alloreactive T help (Th)1 effector cells cause damage to the liver and gastrointestinal tract but prevents lung injury mainly induced by IL-4-producing Th2 effector cells. 29,30 To investigate the impact of Ezh2 on effector T-cell differentiation, we recovered donor T cells from BALB/C mice receiving B6 mouse-derived WT and T-KO T cells at various time points after transplantation.…”
mentioning
confidence: 99%